2022
DOI: 10.1021/acsnano.2c08911
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport in Graphene/Pb0.24Sn0.76Te Heterostructures: Finding a Way to Avoid Catastrophe

Abstract: While heterostructures are ubiquitous tools enabling new physics and device functionalities, the palette of available materials has never been richer. Combinations of two emerging material classes, two-dimensional materials and topological materials, are particularly promising because of the wide range of possible permutations that are easily accessible. Individually, both graphene and Pb1-xSnxTe (PST) are widely investigated for spintronic applications because graphene’s high carrier mobility and PST’s topolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…However, SnTe was mainly used to approximate PbSnTe due to the expense of the calculations. Additional details can be found in the Supporting Information or in the previous work in reference 21, where it was demonstrated that SnTe, PbTe, and PbSnTe all behave similarly in this context, where the dominant heterostructure behavior was from a meeting of polar and non-polar surfaces.…”
Section: Theory Methodsmentioning
confidence: 92%
See 4 more Smart Citations
“…However, SnTe was mainly used to approximate PbSnTe due to the expense of the calculations. Additional details can be found in the Supporting Information or in the previous work in reference 21, where it was demonstrated that SnTe, PbTe, and PbSnTe all behave similarly in this context, where the dominant heterostructure behavior was from a meeting of polar and non-polar surfaces.…”
Section: Theory Methodsmentioning
confidence: 92%
“…Pb 0.24 Sn 0.76 Te (111) (PST) topological crystalline insulator (TCI) films were grown to a thickness of 7 nm on GaAs (001) by molecular beam epitaxy using methods described previously. [21] The stoichiometry was chosen to maximize the bulk bandgap while maintaining the TCI behavior, as discussed in depth elsewhere. [21,22] Graphene was grown by low pressure (5-50 mTorr) chemical vapor deposition on copper foiled at 1030 °C under flowing H 2 and CH 4 gas.…”
Section: Growth Methodsmentioning
confidence: 99%
See 3 more Smart Citations